2012
DOI: 10.1002/ana.22643
|View full text |Cite
|
Sign up to set email alerts
|

Genistein in Sanfilippo disease: A randomized controlled crossover trial

Abstract: Genistein at 10mg/kg/day effectively reduces urinary excretion of GAGs and plasma HS concentration in patients with MPS III. However, the absolute reduction in GAGs and in HS is small and values after 12 months of treatment remain within the range as observed in untreated patients. No clinical efficacy was detected. Substantially higher doses of genistein might be more effective as suggested by recent studies in animal models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 33 publications
1
71
0
1
Order By: Relevance
“…Two other studies with MPS III patients indicated that some disease-linked parameters and symptoms (like hair morphology and urinary GAG level) could be improved during GET IT (Malinova et al 2012), while changes in other parameters (like a disability score) were not observed (Delgadillo et al 2011). Nevertheless, results of very recent double-blinded placebo-controlled clinical trial, which evaluated efficacy of GET IT for MPS III, indicated that despite the fact that a statistically significant decrease in GAG levels in urine and plasma was found when genistein was administered at the dose of 10 mg/kg/day, no statistically significant clinical improvement could be observed during 6-month treatment (de Ruijter et al 2012). Therefore, it was suspected that higher doses of genistein might be considerably more efficacious (Wegrzyn 2012), especially since the most positive effects were reported in mice at genistein dose of 160 mg/kg/ day (Malinowska et al 2010), which is more than 10 times higher than the highest dose used to date in published human studies (Malinova et al 2012).…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 99%
“…Two other studies with MPS III patients indicated that some disease-linked parameters and symptoms (like hair morphology and urinary GAG level) could be improved during GET IT (Malinova et al 2012), while changes in other parameters (like a disability score) were not observed (Delgadillo et al 2011). Nevertheless, results of very recent double-blinded placebo-controlled clinical trial, which evaluated efficacy of GET IT for MPS III, indicated that despite the fact that a statistically significant decrease in GAG levels in urine and plasma was found when genistein was administered at the dose of 10 mg/kg/day, no statistically significant clinical improvement could be observed during 6-month treatment (de Ruijter et al 2012). Therefore, it was suspected that higher doses of genistein might be considerably more efficacious (Wegrzyn 2012), especially since the most positive effects were reported in mice at genistein dose of 160 mg/kg/ day (Malinowska et al 2010), which is more than 10 times higher than the highest dose used to date in published human studies (Malinova et al 2012).…”
Section: Efficacy Of Srt In In Vitro Studies Experiments With Animalmentioning
confidence: 99%
“…After digestion, the samples are loaded into the LC-MS/MS for quantitation, and the results are compared with control samples (Figure 2). The LC-MS/MS method for analysis of disaccharides not only shows sensitivity and specificity for detecting all subtypes of MPS but also can monitor therapeutic efficacy in MPS patients and animal models [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. This method has an advantage of being both GAG-specific and quantitative.…”
Section: History Of Gag Assay By Tandem Mass Spectrometry (Ms/ms)mentioning
confidence: 99%
“…Total urinary GAG, a potential biomarker for MPS, is measured spectrometrically by using DMB [17,18,33,34] or Alcian blue [23,35]; however, these methods cannot be applied to blood without protease treatment, since protein in the specimen hinders the binding of the dye to the GAG. Moreover, the dye itself tends to decompose, leading to a high background and false positive results.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Gen has been recently proposed as therapy for Sanfilippo disease. In combination with an anti-CD19, it was also found to be an active agent for the control of leukemic human B lymphocytes [8].…”
Section: Introductionmentioning
confidence: 98%